Fire prevention and risk aversion among informal urban dwellers in Cape Town - Kanyinji, Rabson (School of Economics, 2015)
This paper attempts to provide experimental evidence on fire prevention and risk aversion among urban informal settlers using lottery choice data with real monetary prizes. The paper estimates the risk attitudes of a sample of 174 individuals from an informal housing development in Cape Town. The empirical analysis is performed within the expected utility theory specification, assuming constant relative risk aversion (CRRA) defined over the lottery prize. We tests the hypothesis that risk averse individuals will take precautionary measures in as far as possible to mitigate the risk of fire to their household. We find that individual-level fire prevention measures that are within the means of the households to effect, such as making sure that matches, lighters and paraffin are kept out of reach of children, is correlated with risk aversion, but measures, such as building of homes at least 3-5 meters from the neighbours, does not seem to be within the choice set of low-income informal dwellers. Our results further indicate that subjects who engage in fire prevention/fire safety strategies that require the "most effort" (that are most effective and costly) are significantly more risk averse relative to subjects engaging in fire safety measures that need "least effort". Contrary to expectation, distance from the main road, informal electricity connection, and the use of paraffin for lighting, heating and cooking are not correlated with risk aversion, indicating that irrespective of the risk profiles of decision makers, low-income households are often forced to make choices that increase their exposure to fire hazards.